Manajemen Satuan Pendidikan Dalam Mewujudkan Profil Pelajar Pancasila di SMA Negeri 10 Palembang - Gunarti Gunarti; Bukman Lian; Nuril Furqan (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This research was carried out to describe and analyze the management of educational units in realizing the Pancasila student profile, describing and analyzing the factors that hinder and support the management of academic units in learning the Pancasila student profile. This research used a qualitative descriptive method with eleven informants and data collection techniques through interviews, observation, and documentation. The data obtained was analyzed by reduction, data presentation, and conclusions. The results of this research show that the management of the educational unit succeeded in realizing the Pancasila student profile through P5; the supporting factors are internal and external. Inhibiting factors are a lack of understanding of educators, limited PBM time, teaching teams that are constantly changing, lack of student interest, and students are still passive, limitations of the project team designing teaching modules, learning strategies that are not varied, and lack of parental support and teacher attention. Conclusion: The management of the educational unit has succeeded in realizing the Pancasila student profile Keywords: Education Unit, Management; Pancasila Student Profile.